Application of structural equation and servqual in a health service (2014)
The aim of this contribution is to check the relationship between the dimensions of the overall operational quality perceived by users; by the sensitivity of the services, since constantly checked daily and the particular characteristics in operation. Also, illustrate the behavior and benefits of structural equations and model servqual in organizations that seek to provide a service that builds competitive advantage through the adoption of tools aimed at improving the quality of their processes and improve the level of performance against users. The research was conducted from the author's interest to achieve greater applicability of these in the companies providing health services in of Manizales (Colombia), which has not been studied so far and are not major bibliographical reference reports on it, something that makes it a topic of interest.